Chronic Tobacco Snuff-Induced Columellar Squamous Cell Carcinoma: A Case Report - Kınıs, Vefa; Gun, Ramazan; Bakır, Salih; Yorgancılar, Ediz; Topcu, İsmail; Fırat, Ugur (Fırat University, 2011)
In this article, we presented a 57-year-old woman with a history of snuff abuse for 16 years and developed squamous cell carcinonoma in the columellar skin. Primary cancer of nasal columella is extremely rare. This is a very agressive tumor and if not resected adequately it can easily spread to adjacent structures.. These tumors should be treated radically. The tumor was resected and defect was reconstructed with left nasolabial sulcus flap in this case. Close follow-up is required because of high recurrence rate. We try to discuss the behavior of these tumors, staging, treatment modalities and prognostic factors.

Bu yazıda 16 yıldır burnuna tütün çekme hikayesi olan ve kolumellar ciltte skuamoz hücreli kanser gelişen 57 yaşında bayan hastayı sunduk. Nazal kolumellanın primer kanseri oldukça nadirdir. Bu çok agresif olan ve yeterince rezeke edilmediğinde kolaylıkla çevre yapılara yayılabilen bir tümördür. Bu tümörler radikal olarak tedavi edilmelidir. Bu vakada tümör rezeke edildi ve oluşan defekt nazolabial sulkus flebiyle rekonstrukte edildi. Yüksek rekürrans oranı nedeniyle yakın takip gereklidir. Bu tümörlerin davranışı, evrelemesi ve tedavi seçeneklerini tartışmaya çalıştık.
Kronik Olarak Buruna Tütün Çekimine Bağlı Skuamoz Hücreli Karsinom: Olgu Sunumu